CONTRIBUTION OF ISLAMIC LAW IN INDONESIAN LEGAL POLITICS - Murdan Murdan (Universitas Islam Negeri (UIN) Mataram, 2019)
Some Indonesian people assume that Legal Policy is not much different from the politicization of law, and some other people conclude that legal policy is the political domination of the law. This view or conclusions about legal policy is high mistake or fault. In the context of Indonesian legal science, the legal policy in the direction of legal policy issued officially by the state and all its attributes to achieve the country or state goals. So, what the mean about the legal policy on Islamic law? The meaning of Islamic LegalPolicy is the contribution of Islamic Law in various legal developments in Indonesia, which aims to help realize or achieve the objectives of the implementation of the Unitary State of the Republic of Indonesia. This paper will discuss and present descriptions of the concepts of Islamic LegalPolicy in Indonesia and the contribution of Islamic Law in the development of Indonesian national Law, which is oriented towards efforts to realize the ideals and objectives of the establishment of the Indonesian Law.